The Influence Training Based on Technology E-learning to Competence Employee in Moderation Gender on PT. Siix Ems Indonesia - Vicka Arvianti,; Mohammad Darul Fadli, Uus; Rosmawati, Ery (Research in Management of Technology and Business, 2025)
The development of sophisticated digital technology in Indonesia has had a major impact on human life, one of which is in the electronics industry sector, human resource management (HR) is included in the aspects of life affected by this development. In this context, training plays a role in ensuring that the workforce is able to adapt to current changes. So that good and relevant competencies can be possessed by every employee to face challenges in the current digital era. The purpose of this study was to determine and evaluate the variables of E-Learning technology-based training on employee competencies at PT. Siix Ems Indonesia which is moderated by gender. The approach used in this study is quantitative descriptive. PT. Siix Ems Indonesia is the population in the current study involving 150 employees and the sample used is 100 respondents. Data obtained by distributing questionnaires were then analyzed using the PLS-SEM method using Smart PLS 4.0 software. The findings of the study showed a positive and significant influence of E-Learning-based training on employee competencies and gender did not moderate the variables of E-Learning-based training on employee competencies